The Role of Hypoxia-Regulated MicroRNA in Cancer - McCormick, R; Robert McCormick (2012)
MicroRNAs (miRNAs) are short, non-coding RNA sequences which regulate gene expression. Regulation is mediated primarily through binding to complementary sites in their un-translated regions which leads to mRNA degradation or translational repression. Hypoxia is a known feature of many tumours, and increased hypoxia is associated with poor prognosis. Hypoxia leads to the up-regulation of many genes involved in a variety of functions including angiogenesis, a shift to glycolytic metabolism, and cell proliferation. This is mediated by the heterodimeric transcription factor HIF (hypoxia inducible factor), which is stabilised in hypoxia. In normoxia, the von-Hippel Lindau protein (VHL) targets HIF for degradation. Mutation in the VHL gene, as is frequently seen in clear cell renal cell cancer (CCRCC), results in constitutive over-expression of HIF and its gene targets, leading to a pro-angiogenic and pro-tumourigenic state. This thesis examined the expression of hypoxia-regulated miRNAs in cancer. The principal aims were to determine gene targets of miR-210, and to explore the effects of its over-expression and knock-down, both in vitro and in vivo. The expression of hypoxia-regulated miRNAs was examined in clinical renal tumour samples with matched normal tissue controls, and correlated with VHL mutation status. It was found that miR-210 targeted the iron sulphur cluster homologue (ISCU) gene, and was responsible for much of its down-regulation in hypoxia. Knock-down of ISCU had consequences on cell metabolism, in particular involving mitochondrial function and iron metabolism. miR-210 was found to be highly over-expressed in clear cell renal tumours (CCRCC), with greater expression seen in tumours with VHL mutations. miR-210 over-expression was also observed in papillary renal tumours, but to a lesser extent than in CCRCCs. miR-210 expression appeared to be correlated with reduced stage and grade, and improved survival. ISCU protein expression in CCRCCs was determined by immunohistochemistry, which showed that its expression correlated negatively with miR-210 expression, suggesting a functional role of miR-210 in vivo.